1994
DOI: 10.1002/ijc.2910570711
|View full text |Cite
|
Sign up to set email alerts
|

Detection of small-cell-lung-cancer cells in bone-marrow aspirates by monoclonal antibodies NCC-LU-243, NCC-LU-246 and MLuCl

Abstract: Despite their high response rate to treatment, virtually all patients with small-cell lung cancer (SCLC) eventually die. More accurate staging procedures may identify patients who might perhaps benefit from novel treatment strategies.Monoclonal antibodies (MAbs) recognize antigens expressed by tumor cells and have thie potential to detect small numbers of infiltrating tumor cells ;at metastatic sites. Many of the antibodies that react with SCLC have been grouped into clusters based on their pattern of reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…2). [8][9][10][11][12]. The results of staining of these 5 preparations are presented in Table 1 (group II, preparations Nos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). [8][9][10][11][12]. The results of staining of these 5 preparations are presented in Table 1 (group II, preparations Nos.…”
Section: Resultsmentioning
confidence: 99%
“…Use of MAb to surface anti- Fig. Indirect immunofluorescence, x 3000, gens of SPC cells disclosed metastases to the bone marrow in 20-50% of patients in whom they had not been detected by cytomorphological investigation [8,11]. Aggregates of small--ceil pulmonary carcinoma cells, stained with MAb H417.1 (preparation No.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence suggests that not only BM contamination by SCLC cells is far more frequent than previously shown by traditional cytohistological methods (Stahel et al, 1985;Leonard et al, 1990;Pasini et al, 1994bPasini et al, , 1995 but also that BM involvement may have clinical relevance (Leonard et al, 1990;Bucher et al, 1994;Pasini et al, 1994bPasini et al, , 1995. Immunocytochemistry is a convenient method for detecting BM micrometastases thanks to its simplicity, reliability and relative low cost (Leonard et al, 1990;Molino et al, 1991;Beiske et al, 1992;Skov et al, 1992;Pasini et al, 1994a), whereas other techniques, such as in vitro cultures of marrow cells (Pollard et al, 1981;Hunter et al, 1987;Everard et al, 1990) or magnetic resonance imaging (Trillet et al, 1989), are cumbersome, time-consuming and expensive.…”
mentioning
confidence: 99%
“…NCAM belongs to a family of membrane-bound, homophilic calcium-dependent glycoproteins involved in both cell-cell and cell-substrate interactions (Keilhauer et al, 1985;Cunningham et al, 1987;Rutishauer et al, 1988;Acheson et al, 1991). They are also expressed in a wide variety of normal tissues, mainly of neural and mesenchymal lineage (Cunningham et al, 1987;Dalseg et al, 1989;Patel et al, 1991;Lanier et al, 1992), as well as in most neuroectodermal and some mesodermal tumours (Patel et al, 1989(Patel et al, , 1991Moolenaar et al, 1990;Tome et al, 1991;Kern et al, 1992;Miettinen and Cupo, 1993;Ledermann et al, 1994;Pasini et al, 1994aPasini et al, , 1995Nakamura et al, 1995). Several isoforms of the molecule have been described that derive from a single copy gene by alternative mRNA splicing (Cunningham et al, 1987).…”
mentioning
confidence: 99%
“…Evidence is accumulating not only that bone marrow microcontamination by SCLC cells is by far more common than assessed by traditional cytohistological methods (Berendsen et al 1988;Trillet et al 1989;Beiske et al 1992) but also that this involvement may have clinical relevance (Leonard et al 1990;Bucher et al 1994;Pasini et al 1994bPasini et al , 1995. In general, the immunocytochemical search for bone marrow micrometastases in SCLC patients has been performed on bone marrow aspirates (BMAs) using monoclonal antibodies (MAbs) directed against tumor-associated membrane antigens or cytokeratin polypeptides (Leonard et al 1990;Beiske et al 1992;Skov et al 1992;Pasini et al 1994a). Immunocytochemistry is the most simple, reliable, and inexpensive technique for detecting neoplastic microlocalizations in bone marrow (Molino et al 1991), whereas other reported methods, such as in vitro cultures of marrow cells (Pollard et al 1981;Hunter et al 1987;Everard et al 1990) or magnetic resonance imaging (Trillet et al 1989), are cumbersome, expensive, and time-consuming.…”
mentioning
confidence: 99%